Respuesta :
14:43
Given zeros are x=-3 and x=2. Now we have to find which of the given function will satisfy the given zeros. To find that we will just plug x=-3 and x=2 to see which choice gives output 0 for both.
Test for A. f(x)=(x-3)(x+2)
f(-3)=(-3-3)(-3+2)=(-6)(-1)=6
Output is not 0 so this can't be the answer.
Test for B.f(x)=(x-3)(x-2)
f(-3)=(-3-3)(-3-2)=(-6)(-5)=30
Output is not 0 so this can't be the answer.
Test for C.f(x)=(x+3)(x-2)
f(-3)=(-3+3)(-3-2)=0(-5)=0
f(2)=(2+3)(2-2)=(5)(0)=0
Output is 0 so this is the answer.
Test for D.f(x)=(x+3)(x+2)
f(-3)=(-3+3)(-3+2)=(0)(-1)=0
f(2)=(2+3)(2+2)=(5)(4)=20
Output is not 0 so this can't be the answer.
Hence final answer is C.f(x)=(x+3)(x-2)